A 122 GHz On-Chip 3-Element Patch Antenna Array with 10 GHz Bandwidth - Lammert, Vincent; Hamouda, Mohamed; Weigel, Robert; Issakov, Vadim (2020 50th European Microwave Conference, EuMC 2020, 2021)
This paper presents the design and measurements of a 122 GHz on-chip patch antenna array in a 130 nm SiGe BiCMOS technology. The array is formed by three rectangular patches in the top metallization layer with the ground plane in the lowest layer. Slots in the patches create a dual-resonance, which helps achieving a simulated bandwidth of 10 GHz and 28% radiation efficiency. The effects of fill structures between the patches and the ground plane are taken into consideration by introducing an equivalent dielectric constant. This makes the array fully compliant with metal density design rules of modern semiconductor processes, while maintaining good performance over a high bandwidth, which makes it attractive for numerous wideband applications, e.g. high-resolution short range radar or high data rate communications.
CRIS-Team Scopus Importer:2021-03-05
Keywords: D-Band; fill structures; metal density; On-chip antenna; patch array; SiGe BiCMOS; wideband